The production of differences and gender inequalities in the school - Ataíde, Sâmara Rodrigues de; Sandano, Wilson (Revista Hipótese, 2019)
This article aims to analyze how gender differences and inequalities act as social markers in the school environment, in their speeches, symbols, representations and daily practices in the construction of female identity.